Effect of land use on the development of slope instability in the Neka-Rood Watershed, Iran (Journal of Nepal Geological Society, 2000)
Land use can be considered as one of the most important parameters in the development of slope instability. It is a factor that continuously changes the land surface condition with time. Therefore, it should be considered when analysing the potential of slope instability and preparing a landslide hazard zonation map. Land use influences the characteristics of land surface and may cause changes in its behaviour towards the processes such as weathering and erosion affecting the inherent properties of the ground.The results show that between 1955 and 1993 more than 30% of the land has been converted from forestland to pastureland in the Neka-Rood Watershed of Iran. This conversion accelerated the slope instabilities in the watershed, where 90% of landslides were recorded in the pastureland and only 8% in the forestland. It was also noted that the geological conditions have greatly influenced the potential of land erosion and consequently the type of land use.